Rule-based Cognitive Modelling for Multimodal Intelligent Tutoring Systems - G. , Manju; K.S., Anilkumar (International Journal of Psychosocial Rehabilitation, 2020)
The work aims to build a rule-based multimodal Intelligent tutoring system. The interface is important as a communication medium. It acts as a problem-solving environment and provides support to student's learning. A good Interface is a mean of an external representation of the system's knowledge and instructional model. A good interface will anticipate the user's action, provide a high level of interaction and make use of metaphors, which in turn requires integration of various advanced technologies. Rule-based models can serve an important role in intelligent tutoring systems (ITS) development. The work focuses on building a multimodal geometry tutoring system. Geometry involves both verbal and visual modes of learning. It is a very good research area to explore multimodal interaction in an intelligent tutoring system.